Problematika Guru Pendidikan Agama Islam Dalam Menerapkan Kurikulum Merdeka Belajar Pada Peserta Didik di SMP Aisyiyah Terpadu Kota Pagaralam - Nabilah, Nurul; Maryanto, M. Agus (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
Islamic religious education is a key component of the national education system in Indonesia. Teachers of Islamic religious education play an essential role in implementing the independent learning curriculum for students at SMP Aisyiyah Terpadu in Kota Pagaralam. However, these teachers face several challenges in applying the independent learning curriculum, such as difficulties in understanding the curriculum concepts, developing relevant teaching materials, and enhancing student motivation. The aim of this study is to identify and analyze the problems faced by Islamic religious education teachers in implementing the independent learning curriculum for students at SMP Aisyiyah Terpadu in Kota Pagaralam. This research employs a qualitative method through in-depth interviews and document analysis. The study involved 10 Islamic religious education teachers at SMP Aisyiyah Terpadu in Kota Pagaralam. The findings indicate that the challenges faced by these teachers include difficulties in understanding the independent learning curriculum concepts, developing relevant teaching materials, and increasing student motivation.